2020
DOI: 10.1002/anie.202002561
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Limiting Factors for Overall Water‐Splitting on Organic Photocatalysts

Abstract: In pursuit of inexpensive and earth abundant photocatalysts for solar hydrogen production from water, conjugated polymers have shown potential to be a viable alternative to widely used inorganic counterparts. The photocatalytic performance of polymeric photocatalysts, however, is very poor in comparison to that of inorganic photocatalysts. Most of the organic photocatalysts are active in hydrogen production only when a sacrificial electron donor (SED) is added into the solution, and their high performances oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 118 publications
0
71
0
Order By: Relevance
“…We also assessed the influence of the dosage of the PyBS‐3 catalyst on the photocatalytic activity since previous studies demonstrated that the mass loading of photocatalyst shows an obvious effect on the photocatalytic performance due to the saturated light absorption after an optimal amount of photocatalyst. [ 25,61 ] As shown in Figure 5b, the actually observed HER only slightly increased from 1.05 to 1.35 mmol h −1 under UV/Vis light irradiation with increasing the dosage of PyBS‐3 from 10 to 25 mg. What's more, the HER unexpectedly decreased from 1.35 to 0.41 mmol h −1 as further increasing the dosage from 25 to 50 mg. Given a fixed HER, a less photocatalyst dosage indicates a higher efficiency of the photocatalyst.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…We also assessed the influence of the dosage of the PyBS‐3 catalyst on the photocatalytic activity since previous studies demonstrated that the mass loading of photocatalyst shows an obvious effect on the photocatalytic performance due to the saturated light absorption after an optimal amount of photocatalyst. [ 25,61 ] As shown in Figure 5b, the actually observed HER only slightly increased from 1.05 to 1.35 mmol h −1 under UV/Vis light irradiation with increasing the dosage of PyBS‐3 from 10 to 25 mg. What's more, the HER unexpectedly decreased from 1.35 to 0.41 mmol h −1 as further increasing the dosage from 25 to 50 mg. Given a fixed HER, a less photocatalyst dosage indicates a higher efficiency of the photocatalyst.…”
Section: Resultsmentioning
confidence: 91%
“…A particular advantage of organic polymers is the designable molecular structure, which allows one to tune, in a broad range, the polymer structures and electronic properties of polymeric semiconductor photocatalysts by using different synthetic strategies and the selection of building blocks. [ 24–26 ] For instance, it has been proved that building a donor–acceptor (D–A) polymer structure is an efficient strategy to enhance the photocatalytic activity of organic polymer photocatalysts, since the electron push–pull system in a D–A polymer can enhance the separation of light‐induced electron/hole pairs. [ 27–29 ] The combination of a polycyclic aromatic donor and an electron‐withdrawing acceptor results in enhanced electron push–pull effect that further increases the separation capability of charge carriers, [ 30–33 ] leading to an enhanced photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] Due to the diversity of monomers and different polymerization routes, many different polymer photocatalysts have been synthesized, 31 but their performance as photocatalysts for hydrogen evolution from water is still lower than for the best inorganic semiconductors. 32 In previous work, a large series of conjugated polymers was synthesized by Suzuki-Miyaura polycondensation and tested as hydrogen production photocatalysts using a high-throughput workflow, showing that the screening allows for the accelerated discovery of high performance photocatalysts. [11][12][13]17 Acetylenelinked polymer photocatalysts and photoelectrode materials have been used for water splitting or pollutants degradation under visible light illumination with good results.…”
Section: Introductionmentioning
confidence: 99%
“…However, a rational design is still elusive as there is still a lack of an in-depth understanding of the processes occurring in a solvated catalyst. 52 The aqueous medium has been shown to ease the dissociation of the diffused excitons at the interface between the organic photocatalyst and water due to higher relative permittivity, but this also means that the degree of solvation of the photocatalyst, as well as the organization of the local environment and its permittivity and polarity when using a sacrificial agent, can impact the thermodynamic force as well as the kinetics of the reactions. This is more striking for porous materials, with porosity that should be beneficial to increase the photocatalyst surface area, but does not always lead to higher activities.…”
Section: Discussionmentioning
confidence: 99%